Effects of Moderate-to-Severe Impairment of the Estimated Glomerular Filtration Rate and of Proteinuria on the Central Hemodynamics and Arterial Stiffness in Middle-Aged Healthy Japanese Men - Hirofumi Tomiyama; Mari Odaira; Chisa Matsumoto; Jiko Yamada; Masanobu Yoshida; Kazuki Shiina; Akira Yamashina (International Journal of Nephrology)
We evaluated the effects of moderate-to-severe impairment of the estimated glomerular filtration rate (eGFR: 15 to 59 mL/min per 1.73 m2) and of proteinuria on the central hemodynamics and the pulse wave velocity (PWV) in 2244 middle-aged healthy Japanese men who were not receiving any medications for cardiovascular diseases or cardiovascular risk factors. The adjusted value of the radial augmentation index was higher in the subjects with proteinuria than in those without proteinuria. On the other hand, this value was similar between the subjects with and without moderate-to-severe impairment of the eGFR. Not only proteinuria but also moderate-to-severe impairment of the eGFR was associated with increase in the adjusted value of the brachial-ankle PWV. Thus, proteinuria was found to be an independent risk factor for abnormal central hemodynamics and increased stiffness of the large- to middle-sized arteries, while moderate-to-severe impairment of the eGFR was associated with an increase of the arterial stiffness, but not with abnormality of the central hemodynamics.